575 Using burden of cancer to promote policy change. (24th April 2018) - Demers, PA; Kim, J; Pahwa, M; Peters, CE; Song, C; Arrandale, VH; Davies, HW; Labrèche, F; Lavoue, J; Nicol, AM; McLeod, CB
Abstract : Introduction: Occupational cancer is poorly recognised due to its long latency among other factors. Burden of occupational cancer projects are an effective tool for drawing attention to the magnitude of the problem and promoting prevention. We present here some major results from the Canadian Burden of Occupational Cancer project and discuss its use for prevention. Methods: Our methods are based on a similar UK project, with several enhancements. The historic labour force was identified using 1961 through 2001 Census data. Occupational exposure prevalence was estimated using CAREX Canada data, allowing calculation of levels of exposure for 44 carcinogens. Relative risks were based on large epidemiologic studies and meta-analyses representative of Canadian exposure circumstances. Standard methods with Levin's equation were used to calculate attributable fractions. Result: Exposure to solar radiation was responsible for the largest number of cancers (4550 basal and squamous cell carcinomas annually, 6.3% of all non-melanoma skin cancer). Asbestos came second with 425 mesotheliomas (80.5% of mesothelioma, including para-occupational, but not environmental, exposure), 1900 lung cancers (8.0% of lung cancer), and smaller numbers of larynx and, ovarian, and suspected other cancers. Diesel engine exhaust was responsible for 560 lung cancers (2.4% of lung cancer) and suspected for 200 bladder cancers (2.7% of bladder cancer). Crystalline silica and welding fumes were responsible for 570 and 315 lung cancers (2.4% and 1.3% of all), respectively. Shiftwork resulting in circadian disruption was suspected for between 460 and 1180 breast cancers (2.0%–5.2% of all), annually. Discussion: Results from the project have begun to be used by Canadian regulatory organisations to establish priorities and by advocacy organisations to raise awareness and push for policy change. These efforts and the input from burden estimates have played a role in the governmental campaign to ban asbestos, now scheduled for 2018.